2017
DOI: 10.18410/jebmh/2017/23
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Uric Acid Levels in Early Second Trimester as an Early Predictor for Preeclampsia

Abstract: BACKGROUND Hypertensive disorders complicate 5-10% of all pregnancies. Screening for these factors in the second trimester of pregnancy will help in early detection of hypertensive disorders of pregnancy, thus enabling. 1. Early identification of patients at risk of developing preeclampsia and eclampsia. 2. Prophylactic medication to prevent hypertension or to reduce its severity. 3. Proper antenatal care. The aim of the study is to study the accuracy of serum uric acid levels in early second trimester (14-20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Also, it was found that in HDP the elevation of uric acid occurs before the onset of hypertension and or proteinuria [13, 14]. There are many reasons for raised serum uric acid levels in women with HDP, which include impaired clearance from kidneys, increased tissue breakdown, acidosis and increased activity of xanthine oxidase/dehydrogenase enzyme [14, 15]. The main reason behind impaired renal clearance of uric acid is reduced glomerular filtration rate, increased absorption and decreased secretion leading to raising serum uric acid levels in women with HDP [14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was found that in HDP the elevation of uric acid occurs before the onset of hypertension and or proteinuria [13, 14]. There are many reasons for raised serum uric acid levels in women with HDP, which include impaired clearance from kidneys, increased tissue breakdown, acidosis and increased activity of xanthine oxidase/dehydrogenase enzyme [14, 15]. The main reason behind impaired renal clearance of uric acid is reduced glomerular filtration rate, increased absorption and decreased secretion leading to raising serum uric acid levels in women with HDP [14].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the serum uric acid level to about to 3 mg/dL or more has been observed during the first trimester in pregnant women, due to higher blood flow in kidney and uricosuric effects of estrogen. 9 Followed by this, an elevation in the serum uric acid level occurs in the third trimester, reaching up to 4-5 mg/dL at term. However, a slightly higher serum uric acid level was observed in HDP prone pregnant women, especially in the first trimester of their pregnancy.…”
Section: Introductionmentioning
confidence: 91%
“…7 Impaired renal clearance of uric acid, elevated breakdown of tissues, acidosis, and an increase in dehydrogenase or xanthine oxidase enzyme were believed to be the reasons for higher levels of uric acid levels in the serum of pregnant women with HDP. 8,9 A reduction in the rate of glomerular filtration is the main reason for impaired clearance of uric acid from kidney, reduction in secretion and elevated absorption results in higher serum uric acid levels in individuals with HDP. A decrease in the serum uric acid level to about to 3 mg/dL or more has been observed during the first trimester in pregnant women, due to higher blood flow in kidney and uricosuric effects of estrogen.…”
Section: Introductionmentioning
confidence: 99%
“…SUA levels increase in HDP due to tissue breakdown, acidosis, decreased renal clearance, and increased activity of the xanthine oxidase/dehydrogenase enzyme [ 4 , 5 ]. In the first trimester, uric acid levels are <3 mg/dL due to uricosuria and increased renal blood flow (estrogen effect).…”
Section: Introductionmentioning
confidence: 99%